BMP7 gene polymorphisms are not associated with bone mineral density or osteoporotic fractures in postmenopausal Chinese women - Gao Li-hong; Li Shan-shan; Shao Chong; Fu Wen-zhen; Liu Yu-juan; He Jin-wei; Zhang Zhen-lin (Acta Pharmacologica Sinica, 2017)
Aim: A previous study shows that bone morphogenetic protein 7 (BMP7) gene polymorphisms are associated with bone mineral density (BMD) in 920 European Americans. To determine the association of BMP7 polymorphisms and BMD and osteoporotic fracture susceptibility, we performed a case-control association study in postmenopausal Chinese women with or without osteoporotic fracture. Methods: A total of 3815 unrelated postmenopausal Chinese women (1238 with osteoporotic fracture and 2577 healthy controls) were recruited. BMDs of the lumbar spine 1–4 (L1–4) and proximal femur (including total hip and femoral neck) were measured using dual-energy X-ray absorptiometry. Eight tagging single nucleotide polymorphisms (SNPs) in BMP7 gene, including rs11086598, rs4811822, rs12481628, rs6025447, rs230205, rs17404303, rs162316 and rs6127980, were genotyped. Results: Among the 8 SNPs, rs6025447 and rs230205 were associated with total hip BMD (P=0.013 and 0.045, respectively). However, the associations became statistically insignificant after adjusting for age, height and weight. The TGTG haplotype of BMP7 gene was associated with total hip BMD (P=0.032), even after adjusting for age, height and weight (P=0.048); but the association was insignificant after performing the Bonferroni multiple-significance-test correction. Moreover, the 8 SNPs and 9 haplotypes of BMP7 gene were not associated with L1–4 or femoral neck BMD or osteoporotic fracture. Conclusion: This large-sample case-control association study suggests that the common genetic polymorphisms of BMP7 gene are not major contributors to variations in BMD or osteoporotic fracture in postmenopausal Chinese women.